Hikers' perception of the ecological and social impacts of recreational activities in Gunung Nuang, Malaysia - Ahmad Zawawi, Azita; Bidin, Sheena; Khairi, Nurfarhana; Ahmad Zawawi, Azlyn (Malaysian Forester, 2024)
Forest-based recreational resources are valuable assets that need careful protection from disturbances. The rise in outdoor recreational activities has led to various ecological and social impacts. For instance, hiking can negatively affect the soil, vegetation, water, and wildlife. Research indicates that Gunung Nuang has been significantly affected by recreational activities, leading to erosion of its hiking trails. Understanding hikers' perceptions is essential for developing effective management strategies to preserve these natural resources for future generations' enjoyment. In this study, a rapid assessment was conducted to evaluate the recreational impacts on the trails and selected campsites at Gunung Nuang. Utilizing the data collected from the rapid assessment, questionnaire was developed and distributed using an online platform to gauge hikers' perceptions of the observed impacts at the site. The study further discusses how these impacts might affect hikers' experiences. In total, 189 valid responses were gathered from individuals who hiked Gunung Nuang between 2019 and 2023. The research findings highlighted that most respondents had greater concerns about the social impacts of hiking compared to the ecological ones. Additionally, hikers' tolerance towards these recreational impacts varied depending on their educational backgrounds. The research findings also revealed that recreational impacts can significantly shape hikers' overall experiences. By assessing the effects of recreational activities, authorities can devise effective strategies for managing and preserving natural resources. The insights derived from this study are vital in crafting educational initiatives that encourage responsible and sustainable hiking practices.